Force Sensor for Multiphysical Quantity Detection and Its Validation Through Random Test - Wang, Chieh-Cheng; Hung, Chen-Hao; Chen, Yu-Wen; Lo, Cheng-Yao (IEEE sensors journal, 2025)
This study aimed to develop a force sensor with decoupling function for normal and shear forces and also for normal and shear angles. The sensor contained five capacitors in shapes of diamond and triangles for compact footprint. In applications, the normal force was limited to the central diamond-shaped capacitor by spacers. In contrast, the shear force was limited to the surrounding four triangular capacitors. To realize the force and angle decoupling, a workflow was proposed and validated through both ideal and Random tests. Numerical simulation, fabrication, measurement, and analysis were thoroughly conducted in this work. The sensitivity for normal and shear force on average was 0.776 and 0.330 pF/N, respectively; and reliable accuracy was demonstrated with limited tolerance (normal and shear force on average of −6.79% and −6.65%, respectively). In addition, the tolerance for shear and normal angle on average was 0.19° and 0.04°, respectively, outperforming the existing demonstrations in literature with characteristic comparisons.